Strikes and Doctors- psychosocial and ethical dilemmas (Bangladesh Journal of Bioethics, 2015)
This paper is a commentary on whether doctors have the right to strike work or not while keeping in mind, psychosocial and ethical implications of the same. Certain guidelines and criteria that may be applicable when examining doctors on strike are elucidated and discussed. DOI: http://dx.doi.org/10.3329/bioethics.v5i3.21534 Bangladesh Journal of Bioethics 2014; 5(3):23-25